ANALISIS PENGARUH PAJAK DAERAH, DANA PERIMBANGAN, DAN LAIN-LAIN PENDAPATAN YANG SAH TERHADAP KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - ARDI, LIA EVIANA; AMELIA, RIZKY WINDAR; ., SUSYANTI (KIAT BISNIS, 2016)
This research aim to to test the influence of area Iease, counter balance fund, and others valid earnings to finance performance of at Local Government Regency in Provinsi of Central Java of budget year 2015. Population And sampel in this research is entire regency and town of exist in Provinsi of Central Java consisted of by 29 regency and 6 town, what have publicized the report realize the revenue plan and area expense in the year 2015 in Monetary Board of Examiners Republic of Indonesia. Model the data analysis used by doubled regresi. Test the classic assumption used by is test normalitas, test the multikolinearitas, and test the heteroskedastisitas. and hypothesis Examination used by test t , test the f, and coefficient determinasi. Result of this research indicate that (1) area Iease, counter balance fund, and others valid earnings by simultan have an effect on to finance performance of at local government regency in Provinsi Central Java. (2) area Iease by parsial have an effect on to finance performance at local government regency in Provinsi Central Java. (3) Fund of counter balance have an effect on to finance performance at local government regency in Provinsi Central Java. (4) valid earnings others not have an effect on to finance performance at local government regency in Provinsi Central Java Keyword: Area Iease, counter balance fund, valid earnings others, and finance performance.